Real-time steering of curved sound beams in a feedback-based topological acoustic metamaterial. (15th May 2021) - Sirota, Lea; Sabsovich, Daniel; Lahini, Yoav; Ilan, Roni; Shokef, Yair
Highlights: Metamaterial with embedded feedback control mechanism for autonomous sound navigation. Real-time sound pressure field shaping, mimicking quantum topological wave phenomena. Two-dimensional acoustic beam guiding along artificial programmed curved trajectories. Topological protection keeps beams localized on the trajectories despite sharp turns. A tool to realize non-local, nonlinear, time dependent or non-reciprocal interactions. Abstract: We present the concept of a feedback-based topological acoustic metamaterial as a tool for realizing autonomous and active guiding of sound beams along arbitrary curved paths in free two-dimensional space. The metamaterial building blocks are acoustic transducers, embedded in a slab waveguide. The transducers generate a desired dispersion profile in closed-loop by processing real-time pressure field measurements through preprogrammed controllers. In particular, the metamaterial can be programmed to exhibit analogies of quantum topological wave phenomena, which enables unconventional and exceptionally robust sound beam guiding. As an example, we realize the quantum valley Hall effect by creating, using a collocated pressure feedback, an alternating acoustic impedance pattern across the waveguide. The pattern is traversed by artificial trajectories of different shapes, which are reconfigurable in real-time. Due to topological protection, the sound waves between the plates remain localized on the trajectories, and do not back-scatter by the sharp corners or imperfections in the design. The feedback-based design can be used to realize arbitrary physical interactions in the metamaterial, including non-local, nonlinear, time-dependent, or non-reciprocal couplings, paving the way to unconventional acoustic wave guiding on the same reprogrammable platform. We then present a non-collocated control algorithm, which mimics another quantum effect, rendering the sound beams uni-directional.